Analisis Perubahan Waktu dan Tekanan Injeksi terhadap Massa dan Kualitas Produk pada Proses Injection Moulding - Serfandi, Dina Novera; Fahmiy, Muh Ilham; Hidayati, Alfiana Nur; Prayogo, Dhanang Suryo; Sulistyono, Sulistyono (Jurnal Mekanik Terapan, 2025)
The plastic injection moulding process is a dominant manufacturing method for producing high-precision components. Final product quality is highly dependent on process parameters, particularly injection time and injection pressure. This study aims to quantitatively analyze the influence of these parameters on product weight and quality, specifically in mitigating common defects such as shrinkage and short shots. Utilizing polypropylene material, a factorial experimental design was implemented by varying injection time 3,5 s, 4 s, 4,5 s and pressure 36 bar, 37 bar, 38 bar. Each parameter combination was replicated five times to ensure data validity. Product weight was measured using a digital scale, and visual quality was manually evaluated. The findings indicate that increases in injection time and pressure significantly enhanced product weight and reduced defects. An optimal combination of a 4 s injection time and 37 bar pressure was identified, yielding products with consistent weight and superior visual quality. These results offer practical guidance for optimizing production processes and improving efficiency. Keywords: Injection Moulding, Injection Time, Injection Pressure, Product Quality.